Transition et paysage. Analyse des projets de fin d’études de la promotion 2019 de l’École nationale supérieure de paysage - Benoît Dugua; Auréline Doreau; Mégane Millet Lacombe (Projets de Paysage)
The notion of environmental transition is a major scientific and public issue that seems to have superseded that of sustainable development. Uncertainty, complexity, resilience, adaptation, and vulnerability are all notions that accompany the common vocabulary relating to environmental transition and largely permeate the practice and teaching of landscape architecture. The article deals with three issues : (1) How to renew training in landscape architecture in a context of climate change ? (2) What consideration should be given to transition issues in the final year projects at the École Nationale Supérieure de Paysage (ENSP) of Versailles ? (3) What is the contribution of landscape project design as a fundamental skill for graduates in landscape architecture to address transition issues ? The study of ENSP final year projects initiated in the mid-1970s as the culmination of training in landscape architecture are particularly enlightening. The survey is mainly based on a cross-sectional analysis of the forty or so final year projects of the class of 2019, illustrated by a more detailed examination of some of the projects. It is the semantics describing project targets which integrate transition issues that we seek to reveal here. The article starts by briefly retracing the evolution of training in landscape architecture at the ENSP to explain the nature of the historic relations between the landscape and transition. We review the effects of the Chair of Landscape Architecture and Energy, created in 2015 at the ENSP, which marked a new stage in the convergence between landscape architecture and the environmental transition. This exploratory work, carried out at the Laboratoire de recherche en projet de paysage (Larep) in connection with the ENSP Chair of Landscape Architecture and Energy, finally opens up new prospects concerning the historical evolution and inclusion of the issues of environmental transition in the teaching of landscape architecture in Versailles.